Urgensi Pengembangan Keterampilan Penyuluh Agama dalam Meningkatkan Kompetensi Pengolahan Database di KUA Kecamatan Tanete Riattang Kabupaten Bone - Nurul Faizah Kamaruddin; Sulfiana Sulfiana; A. Nurul Azizah Nabilah Halim (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Over the past few decades, technological and information innovation has become increasingly advanced and developed, this has also encouraged increased competency for religious instructors in processing databases. This technological development also has an impact on the Tanete Riattang District KUA agency in the field of religious extension to use website-based technology to make data processing easier. Therefore, it is necessary to develop the skills of religious instructors in increasing their database processing competence. This research aims to explain how important and necessary it is to develop the skills of religious instructors in improving database processing competence. The method used in this research is a descriptive qualitative research method by collecting research data and information through observation, interviews and literature study. The results of the research show that developing the skills of religious instructors in improving database processing competency in the KUA, Tanete Riattang District, Bone Regency is very important and requires immediate attention, because this competency is one of the competencies that religious instructors must have.